Efeito do treino de curta duração no alcance manual de lactentes a termo e suas implicações clínicas - Cunha, Andréa Baraldi (2014)
Objectives: Part I) To verify the effect of short-term training on reaching behavior in fullterm infants at the onset of reaching. Part II) To know the behavior of reaching, the reaching training protocols in full-term and preterm infants and to adjust these training for children with cerebral palsy (CP). Methods: In Part I, it was conducted a randomized controlled trial. 30 healthy infants at 3-4 months of age (M =14.0 ±1.6 weeks of age) were randomly assigned to: 1) reaching training group; 2) social training group (control group). The infants were submitted into 3 assessments (kinematics and qualitative) at 45° reclined position (until 5 days after the onset of reaching): 1) Pre-training, before the first session of training; 2) Post-training 1, after the first session of training, at the same day; and 3) Posttraining 2, after three sessions of training, at the following day. To perform the reaching training and social training, the infants were submitted into three short-term sessions of training, one performed on the first day and the two performed on the second day. All infants were seated reclined 45° in the researcher s lap. The infants of training group received three activities of interaction with the object under serial practice (i.e.: ABC, ABC, ABC) in each session. The infants of social group received no reaching training or stimuli for their upper limbs of each session. The variables considered were: characterizing the sample, the total reaching frequency, distal adjustments (hand orientation, hand opening, and surface of the hand contact), and spatio-temporal variables (duration of movement, mean velocity, straightness index, deceleration index, and movement unit). In Part II, we performed a literature review on: the reaching behavior in infants with typical developmental, preterm infants and infants with CP from 0 to 2 years of age; the main techniques of reaching assessment; models of reaching training protocols (immediate and short-term effects) developed for full-term and preterm infants and; on a way of adjusting reaching training for children with CP in clinical practice. Results: In Part I, a training session was effective in increasing the number of reaches and the percentage of reaches with ventral hand, and decreasing the percentage of reaches with closed and dorsal hand. In addition, three training sessions resulted in changes in the spatio-temporal variables (with shorter and more fluent reachs) and increased the percentage of reaches with vertical hand. For Part II, it was highlighted the importance of determining immediate, short, medium and long term goals, planning the therapeutic procedures directed to the goals. In addition, to use and adapt existing training protocols to intervene in infants at risk and / or diagnosis of CP, and others. Conclusions: A few short training sessions under serial varied condiction were effective in improving the reaching performance, such as changes in the number of reaches, in distal adjustments and spatio-temporal reaching variables. These results reflect the flexibility of the perceptual-motor skills development and the important role of experience in the improvement of motor behavior in infants. Furthermore, to direct the interventions to the functional objectives and, to use and adapt existing training protocols, may provide to the professionals one more tool of intervention in infants at risk and / or established diagnosis of CP.